The criminal liability of child soldiers in international criminal law : does restorative justice offer a balance between the rights of the victim and the rights of the child perpetrator? - De Villiers, Isolde (University of Pretoria, 2015)
Dissertation (LLM)--University of Pretoria, 2014.